The Dynamics Of Students' Self-Confidence Through A Combination Of Self-Monitoring And Role-Playing Tecniques In Group Counseling - Nur Zain Aulia; Uli Makmun Hasibuan; Keysah Ramadian; Yolanda Ayu Kirana (Indonesian Journal of Communication and Social, 2026)
This study examines the dynamics of self-confidence among secondary school students by applying a combination of self-monitoring techniques and role-play in group counselling sessions. Low self-confidence among adolescents is a problem that has a significant impact on the quality of their social interactions and academic achievement. This study was conducted at Pertiwi Secondary School in Medan during the second semester of the 2025/2026 academic year, involving four students from Years 7 and 8. A descriptive qualitative method was used, with data collected through observation, self-monitoring sheets, and transcripts of the group counselling process. The results indicate that the combination of self-monitoring techniques and role-play within a group counselling framework encouraged students to identify situations that trigger low self-confidence, develop greater self-awareness, and directly practise self-assured behaviour through simulated real-life scenarios. The group dynamics process strengthened motivation and a sense of security among participants, thereby enabling the organic internalisation of self-confidence values. This research makes a practical contribution to school guidance and counselling services, particularly to the design of effective, context-specific interventions based on behavioural techniques for adolescents.